Learning environments in higher education: Their adaptability to the 4th industrial revolution and the ’social transformation’ discourse - Krishnannair, A.; Krishnannair, S. (South African Journal of Higher Education, 2021)
The South African higher-education sector is currently undergoing a significant phase in its transition. The phase is marked by a sense of uncertainty felt across institutions and entities that make up the sector. This uncertainty, to a large extent, is brought about by the socio-political realities the transition entails. Compounding this situation is the advent of the 4th Industrial Revolution (Hadden), a phenomenon to which the higher-education sector needs a heightened degree of adaptability. The learning environments provided by the higher-education sector are therefore crucial in terms of advancing the cause of positive social change as a realisable educational objective. Against this backdrop, this conceptual article examines the issue of social change as a moral imperative. The purpose is therefore to contribute to the 4IR discourse currently evolving in the context of South African higher education and its social change agenda, with cognitive capitalism as a theoretical lens. Significant scholarly work has been done on the issue of technological advancement and its implications for the social practice of education. However, a concerted effort has not been undertaken to examine the 4IR as an inevitable educational experience with potential to be both materialistically transformative and morally enslaving. The article concludes that, as 4IR unfolds into a magnificent event and starts to control every aspect of human life in general, and education in particular, the moral and ethical affirmations that support the experience of education may run into troubled waters.